2019
DOI: 10.1111/jvh.13133
|View full text |Cite
|
Sign up to set email alerts
|

High sustained virologic response in genotypes 3 and 6 with generic NS5A inhibitor and sofosbuvir regimens in chronic HCV in myanmar

Abstract: Exclusive HCV therapy clinical trials with genotype 6 patients in high prevalence areas have been sparse. We analysed the safety and efficacy of two generic, pangenotypic NS5A/NS5B combination oral DAA regimens, primarily in genotypes 3 and 6, in a real‐world setting: (a) daclatasvir/sofosbuvir (DCV/SOF) ± ribavirin (RBV) and (b) Velpatasvir/sofosbuvir (VEL/SOF ± RBV). Between December 2015 and November 2017, data from 522 patients were analysed, 311 of whom were treated with DCV/SOF ± RBV for 12/24 weeks (gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Thus, the results are not readily applicable to large populations with this genotype in endemic areas. In our cohort of 166 patients with genotype 6 infection, treatment with DAC + SOF, LDV/SOF, and SOF/VEL resulted in remarkably high SVR rates, approaching the rates reported in clinical trials and other real-world experiences [11,25,26,33]. DAC + SOF and LDV/SOF yielded above 95% SVR12 rates for the treatment-naïve group and the non-cirrhotic group, while SOF/VEL provided 100% SVR12 rates regardless of cirrhotic status and prior treatment experience.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, the results are not readily applicable to large populations with this genotype in endemic areas. In our cohort of 166 patients with genotype 6 infection, treatment with DAC + SOF, LDV/SOF, and SOF/VEL resulted in remarkably high SVR rates, approaching the rates reported in clinical trials and other real-world experiences [11,25,26,33]. DAC + SOF and LDV/SOF yielded above 95% SVR12 rates for the treatment-naïve group and the non-cirrhotic group, while SOF/VEL provided 100% SVR12 rates regardless of cirrhotic status and prior treatment experience.…”
Section: Discussionmentioning
confidence: 61%
“…While the real-world data of DAA therapy for chronic hepatitis C have been reported mostly from western countries [14][15][16][17][18][19][20][21][22], there is a paucity of Asian data concerning DAAs [23][24][25][26][27]. Management of HCV in Asian countries continues to be challenging for a variety of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Generic drugs and their combinations produced by companies under the license of the Medicines Patent Pool and prequalified by WHO and/or other regulatory authorities have been shown to generate similar results to the original compounds, with similar safety and tolerability. [157][158][159][160][161][162][163][164][165][166][167] The panel recognises the heterogeneity of per capita incomes and health insurance systems across Europe and in other regions, and therefore the constraints that may necessitate continued utilisation of regimens described in previous versions of these recommendations but no longer recommended. In settings where none of the IFN-free, ribavirin-free options proposed in this document are available, options proposed in previous versions of these recommendations remain acceptable for patients likely to respond to these regimens until new DAAs become available and affordable; see prior EASL Recommendations on Treatment of Hepatitis C. 120,[168][169][170][171] In particular, in many lowand middle-income countries where the pangenotypic DAA combinations recommended in the present document are not available and/or not affordable, the combination of generic sofosbuvir and daclatasvir is safe and well tolerated and provides high SVR rates at a very low price.…”
Section: Treatment Of Chronic Hepatitis C In Patients Without Cirrhosmentioning
confidence: 99%
“…The effectiveness of decentralized care was previously demonstrated by a study in Columbia, where they found no significant differences in the treatment outcome using SOF-LDV whether administered by nurse practitioners, point-of-care physicians, or specialists (84-89%). 33 Similarly, a study from Pakistan showed that with a simplified HCV testing, SOF-RBV therapy, and monitoring by local healthcare workers resulted in an SVR of 83% with a relatively low 10% loss to follow-up. 34 Admittedly, this study has several limitations.…”
Section: Discussionmentioning
confidence: 99%